Poetics and the study of (African) literature: forms and functions of language in literary criticism - Sola Afolayan; Olumide Ogunrotimi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Most likely, many literary scholars first encounter the word poetics when reading Aristotle’s celebrated treatise which attempts to give a descriptive template to (dramatic) literature. In modern times the word seems to have been transformed beyond the simplistic frame that Aristotle gave it. Interestingly, the emergence of the linguistic and critical avant-gardes like de Saussure, Chomsky, Jakobson, Halliday, Todorov, and Scholes, brought fresh and radical insights into the world of language/literary studies. Hence, as poetics is applied in linguistic/literary discourse today, it gives prominence to the study of language as a component of literature on one hand, and on the other, it provides indelible insights into what literature does to language expressions when they find definitive stance in the form. Considering poetics as indexical compass in the evaluation of literature, this essay probes into the applications of the term in literary criticism, taking-off from the standpoints of linguistic aestheticians who have somewhat attempted to apply it. The analogous result of this ambition is suggestive of literary theory. This then raises the question of the applicability of the several poetics-oriented theories to the evaluation of African literary aesthetics, which from the post colonial angle, is unparaphraseably extraneous to the scientific critical postulations of the West.